2010
DOI: 10.1165/rcmb.2008-0403oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Formoterol on Contraction and Ca2+ Signaling of Mouse Airway Smooth Muscle Cells

Abstract: Formoterol, a long-acting b 2 -receptor agonist, is used to relieve bronchial constriction. However, formoterol is often a racemic formulation, and contains both (R,R)-and (S,S)-enantiomers. Because the activity of each isomer is poorly defined, the mechanisms by which formoterol relaxes smooth muscle cells (SMCs) of intrapulmonary airways are not well understood. Consequently, we compared the effects of (S,S)-, (R,R)-, and racemic formoterol, as well as (R)-albuterol, on the contraction and Ca 21 signaling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 25 publications
(57 reference statements)
2
31
0
Order By: Relevance
“…The transient induction of Ca 21 oscillations indicates that IP 3 is rapidly metabolized. Similar results were found in mouse airways (35).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The transient induction of Ca 21 oscillations indicates that IP 3 is rapidly metabolized. Similar results were found in mouse airways (35).…”
Section: Discussionsupporting
confidence: 88%
“…However, the specifics of this action vary with species and agonist. Isoproterenol appears to slow Ca 21 oscillations by inhibiting the open probability of the IP 3 R, whereas formoterol appears to act initially on Ca 21 sensitivity of mouse airways (35).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, Tan and Sanderson [46] have demonstrated that TAS2R agonists reversed bronchoconstriction by reducing the frequency of calcium oscillations and calcium sensitivity using mouse lung tissues. A similar mechanism has been reported in β 2 AR-induced bronchodilation as shown in previous research [2,45,46]. Taken together, the results in the current study implied that genetic variation in the TAS2R gene affects the airway reversibility by varying the degree of calcium oscillation and sensitivity of lung tissues.…”
Section: Discussionsupporting
confidence: 91%
“…Asthma is a chronic inflammatory disorder characterized by variable airflow obstruction and hyperresponsiveness of bronchi to different stimuli [1,2,3]. Most asthma types can be well controlled by current asthma medication, including inhaled corticosteroid with or without long-acting β 2 -agonists, leukotriene antagonists, theophylline, tiotropium, and even omalizumab; however, approximately 5−10% of all patients fail to achieve control despite the availability of optimal asthma treatments [4], leading to a great burden on health costs [5].…”
Section: Introductionmentioning
confidence: 99%